161k views
3 votes
-14.06+(-26.13)= what is my answer

2 Answers

5 votes
-40.19 THATS the answer
User Mikael Gueck
by
5.5k points
1 vote

Answer:

The value of -14.06 + (-26.13) is -40.19.

Solution:

From question, given that the expression is

= -14.06 + (-26.13)

By removing the parenthesis the above equation becomes, we get

= -14.06 – 26.13

Taking -1 as a common term in above expression, we get

= -1(14.06 + 26.13)

On simplifying the above expression, we get

= -1(40.19)

On removing the parenthesis, the above equation becomes

= -40.19

Hence value of the expression -14.06+(-26.13) is -40.19.

User Firedrawndagger
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.